2021
DOI: 10.2169/internalmedicine.6810-20
|View full text |Cite
|
Sign up to set email alerts
|

Contradictory Responses to the COVID-19 Pandemic in Amyotrophic Lateral Sclerosis Patients and Their Families and Caregivers in Japan

Abstract: Objective The coronavirus disease 2019 (COVID-19) pandemic has resulted in a shortage of medical resources, including ventilators, personal protective equipment, medical staff, and hospital beds. We investigated the impact of COVID-19 in amyotrophic lateral sclerosis (ALS) patients, their families, caregivers, and medical experts. Methods We conducted a nationwide ALS webinar about COVID-19 in May 2020 and sent a questionnaire to those enrolled. Results A total of 135 participants (31 ALS patients; 23 families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Telemedicine’s rapid expansion in response to the pandemic has received much attention [ 13 , 18 22 ], as has alternative approaches for study recruitment and data collection [ 13 , 23 25 ]. A smaller body of questionnaire-based research reports increased anxiety, loneliness, and depression among people affected by ALS, both PwALS and their family caregivers [ 11 , 26 , 27 ]. To date, the experiences of PwALS and their families as they responded to Covid-19 and enacted protective behaviors has received limited attention.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine’s rapid expansion in response to the pandemic has received much attention [ 13 , 18 22 ], as has alternative approaches for study recruitment and data collection [ 13 , 23 25 ]. A smaller body of questionnaire-based research reports increased anxiety, loneliness, and depression among people affected by ALS, both PwALS and their family caregivers [ 11 , 26 , 27 ]. To date, the experiences of PwALS and their families as they responded to Covid-19 and enacted protective behaviors has received limited attention.…”
Section: Introductionmentioning
confidence: 99%
“…Differently from other studies involving caregivers or patients with ALS during the COVID-19 pandemic, the novelty of the present study is that it observed the impact of this situation on caregivers by also taking into account the presence of minors who were meanwhile receiving psychological support, and investigated its indirect effects [26][27][28]. It is already known in the literature how much the well-being or malaise of caregivers affects that of their children and this was all the more accentuated during the Covid-19 pandemic, where the worsening of parents' mental health occurred together with the worsening of children's behavioral health: parents already exposed to a higher risk of distress also due to situations prior to lockdown had compromised being supportive caregivers by compromising children's mental health [29][30][31].…”
Section: Caregivers' Management Of Als During the Covid-19 Pandemicmentioning
confidence: 99%
“…8 Although we have reported the impact of COVID-19 on the mental status of patients with amyotrophic lateral sclerosis, it has also been impacting patients with PD during the pandemic. 78 Several reports have described the impact of COVID-19 on PD, in which mental instabilities have worsened motor symptoms. 61,79 Older people with frailty, depression and anxiety are commonly observed.…”
Section: Relationship Between Pd and Psychological Frailtymentioning
confidence: 99%